EGG HATCHING INCUBATOR - Sandeep S. Kedar1,OmkarV. Koli2,Dinesh A.Choughule2, Ketan H. More2. (International Journal of Innovations in Engineering Research and Technology, 2022)
Incubation is the process of keeping the fertilized eggs warm in order to allow proper development of the embryo into a chick. It is important to control the same factors of temperature, humidity, ventilation, and egg turning. Unsatisfactory results are mostly produced with the improper control of temperature and/or humidity. Improper control means that the temperature or humidity is too high or too low for a sufficient length of time that it interferes with the normal growth and development of embryo.The common problems in incubation are the improper control of temperature that can cause damage to the development of the embryo and decrease poultry’s production. This consumes more labor and time for the owner. Moreover, it is difficult to monitor the incubator using manual monitoring that is very important in incubation.In this study, a poultry egg incubator temperature and humidity controller with SMS notification was designed, constructed and tested to evaluate its performance.